QUALITY OF LIFE OF PATIENTS WITH LOWER LIMB LOSS DUE TO PERIPHERAL ARTERY DISEASE. GENDER INFLUENCE - Елена Михайловна Васильченко (Медицина в Кузбассе, 2018)
Quality of life was analyzed using SF-36 questionnaire in a group of patients with limb loss at the stage of primary prosthesis. It was found that patients without stump prosthesis due to peripheral artery disease have a dramatically reduced quality of life compared to population normal rate in a relevant age group: on physical functioning section; on role limitationsdueto physical health section, onrole limitations due to emotional problems section. Significant differenceswere foundfor a number of indicators of quality of life in the group of patients with postamputation limb defect between male and female patients: summary score on physical functioning section in female was three times lower than in male;summary score on vitality and mental health sections in female waslower for 25 % than in male.